Evaluation of the Implementation of Inclusive Education in Junior High Schools - Putri, Muggia Usmi Eka; Ghani, Abd. Rahman A; Al Jufri, Hamid (ETDC: Indonesian Journal of Research and Educational Review, 2025)
The objective of this study is to evaluate, measure, and prove the gaps in various components—design, installation, process, and product—so that it can provide information for improvement and development related to National Education Standards in building Inclusive Education in Junior High Schools in Tangerang. The evaluation model approach used in this study is the Discrepancy Evaluation Model, or Gap Evaluation Model, developed by Malcolm M. Provus. This research method is a mixed method, not only qualitative descriptive evaluation and quantitative, but also a combination of both. The evaluation subjects were 15 people, including the principal; the vice principal for curriculum, public relations, student affairs, and facilities and infrastructure; teachers; parents; and students. The results indicate that the design aspect, with a discrepancy of 28% in the management standard indicator, falls within the "Medium/Good" category, while the financing indicator, exhibiting a 44% discrepancy, also categorizes as "Medium/Good." Installation Aspect: A gap of 30% in the assessment indicator related to the discrepancy reference is classified as "Medium/Good," whereas a gap of 28% in the assessment facility and infrastructure indicator pertaining to the discrepancy reference is also categorized as "Medium/Good." The process indicator exhibits a 29% discrepancy, categorizing it as “Medium/Good,” while the content indicator shows a 40.4% discrepancy, also classified as “Medium/Good.” The product aspect reveals a 36% gap in the teacher and education personnel competency standard indicator, categorized as “Medium/Good,” while a 25% gap in the graduation competency indicator is also classified as “Medium/Good.”